Opportunities and challenges for the development of the Cerrado bioeconomy: an analysis from the agents of the baru supply chain - Burgos, Andrés; Mertens, Frédéric (Sustainability in Debate, 2024)
Strengthening sociobiodiversity production chains plays a little-understood role in supporting the transition into bioeconomy. This article explores the strengthening of sociobiodiversity chains through the case study of the baru supply chain. Data from semi-structured interviews (n = 114) with various agents involved in the supply chain underwent thematic analysis to understand their perceived opportunities and challenges for strengthening the chain and its contributions to promoting a sociobiodiversity-based bioeconomy in the Cerrado. Results suggest that despite existing opportunities for strengthening the chain, they face numerous challenges to trigger development processes aligned with the sustainable goals of the bioeconomy.